Assessing students’ cooking knowledge before enrolment in a culinary arts program / Mohd Salehuddin Mohd Zahari and Khairil Wahidin Awang - Mohd Zahari, Mohd Salehuddin; Awang, Khairil Wahidin (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA (UiTM), Malaysia, 2014)
The focus of the culinary curriculum in every institution is to provide individuals, especially the young seeking success in the foodservice industry, with a solid base of skills and knowledge in culinary preparation and management. This paper reports the study which identified the new culinary students’ self –assessed knowledge of a few traditional Malay cuisines before enrolling in the culinary arts program, based on secondary school attended. The sample of the population included all first semester students enrolled in January 2007 in the Culinary Division of the Faculty of Hotel and Tourism Management (Penang and Dungun campuses) of MARA University of Technology. The findings of this study revealed that students from vocational schools were more knowledgeable about basic cooking than those students from normal, and other types of secondary school before enrolling in the culinary program. On the other hand, the result also signifies that a substantial number of students especially from normal schools chose to take culinary arts with little knowledge of the general aspects of cooking. With such distinct differences, two conclusions can be drawn. First, a profound lack of basic cooking knowledge among the students from normal and boarding schools means it will take them much longer to acquire knowledge and develop culinary skills in their program. Second, the craft oriented courses taken by the secondary school students clearly provide them with a better knowledge and understanding as well as the skills to advance in their career education program.